Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 7 - Exponential Functions - 7.1 Derivative of f(x)=bx and the Number e - Exercises - Page 327: 23


$$ f'(x)= -4e^{-4x+9}.$$

Work Step by Step

Recall that $(e^x)'=e^x$ Since we have $$ f(x)=e^{-4x+9}$$ then the derivative $ f'(x)$, using the chain rule, is given by $$ f'(x)=e^{-4x+9}(-4x+9)'=-4e^{-4x+9}.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.